Comaprative fatty acid composÄ±tÄ±on of European seabass DÄ±centrarchus labrax (Linnaeus, 1758) farmed in cages in the Aegean Sea and the Black Sea coasts of Turkey - Baki, Birol; Kaya Ozturk, Dilara; Kerim, Murat (Indian Journal of Fisheries, 2019)
The aim of this study was to analyse the fatty acid composition of European seabass Dicentrarchus labrax (Linnaeus, 1758), farmed in marine cages in the Aegean Sea and in the Black Sea coasts of Turkey. The study was conducted between June 2014 and September 2015 using the same feed in all the cage farms. Fish samples representing the stock were collected at regular intervals and morphometric measurements were taken in the laboratory. Fatty acid analyses were carried out by gas chromatography. Biochemical composition of harvested European seabass indicated high dry matter and crude fat values in the Black Sea region and high crude protein and crude ash values in the Aegean region Significant regional differences between fatty acid composition (p